Plasmid-protein relaxation complexes in Staphylococcus aureus. - Novick, R (1976)
Protein-deoxyribonucleic acid relaxation complexes have been demonstrated for six Staphylococcus aureus plasmids out of sixteen examined. Four of these encode stretomycin resistence, have molecular weights of about 2.7 x 10(6), and are isolated as supercoiled molecules that are virtally 100% relaxable by treatment with sodium dodecyl sulfate. It is probable that these four isolates represent a single widely disseminated plasmid species. The other two plasmids showing relaxation complexes have molecular weights of about 3 x 10(6) and encode chloramphenicol resistance. The complexes in these cases are unstable, and it has not been possible to induce more than 50% relaxation by any of the standard treatments. Ten other plasmids do not show detectable complexes. These include three penicillinase plasmids, four tetracycline-resistance plasmids, one plasmid carrying kanamycin-neomycin resistance, and finally, two chloramphenicol-resistance plasmids.